No habit, no listening. Radio and generation Z: snapshot of the audience data and the business strategy to connect with it (Profesional de la información, 2022)
This article describes the most comprehensive study of the relationship between Generation Z and radio carried out in Spain to date, broadening the focus beyond data known from previous research and offering a structural view of the market from the perspective of media economics. An in-depth analysis of data previously unused in academic research, as well as interviews with the managers of various private radio companies (Ábside Media, Atresmedia Radio, Podium Podcast-Prisa Radio, and Grup Flaix), reveals the gradual loss of contact of Generation Z with this medium and highlights the characteristics of the low radio consumption by this cohort in Spain. Among other conclusions, the study identifies some of the factors which may prove relevant to attract this generation to content produced by radio companies, since there is the conviction that there is still time to reverse this situation. Examples include the development of exclusive digital content, brand maximization and community building, content designed and produced by Generation Z for Generation Z, the combination of paid and free access, and media literacy as a transversal public-private factor. This is a need that the sector must address as a whole.